The Vaper's Perspective: A Qualitative Study of E-Cigarette Users and Smokers in Slovenia - Rotar Pavlič Danica; Maksuti Alem; Kopčavar Guček Nena; Albaradi Islam; Stepanović Aleksander (Sciendo, 2024)
The use of e-cigarettes has been rapidly expanding in recent years. The reasons people in Slovenia chose to use electronic cigarettes have not been studied to date. This study examines e-cigarette users' attitudes regarding their health risks.